On skew-symmetric matrices related to the vector cross product in R^7 - Beites, P. D. (2020)
A study of real skew-symmetric matrices of orders 7 and 8, de ned through the vector cross product in R7, is presented. More concretely, results on matrix properties, eigenvalues, (generalized) inverses and rotation matrices are established.